R-Spondin1/LGR5 Activates TGFβ Signaling and Suppresses Colon Cancer Metastasis - Zhou, Xiaolin (Cancer Res, 2017)
Leucine rich repeat containing G protein-coupled receptor 5 (LGR5), an intestinal stem cell marker, is known to exhibit tumor suppressor activity in colon cancer, the mechanism of which is not understood. Here we show that R-spondin 1 (RSPO1)/LGR5 directly activates TGFβ signaling cooperatively with TGFβ type II receptor in colon cancer cells, enhancing TGFβ-mediated growth inhibition and stress-induced apoptosis. Knockdown of LGR5 attenuated downstream TGFβ signaling and increased cell proliferation, survival, and metastasis in an orthotopic model of colon cancer in vivo. Upon RSPO1 stimulation, LGR5 formed complexes with TGFβ receptors. Studies of patient specimens indicate that LGR5 expression was reduced in advanced stages and positively correlated with markers of TGFβ activation in colon cancer. Our study uncovers a novel crosstalk between LGR5 and TGFβ signaling in colon cancer and identifies LGR5 as a new modulator of TGFβ signaling able to suppress colon cancer metastasis.